Evaluating of Tubercullosis Treatment With DOTS Strategy During Covid-19 Pandemic in Boru Community Health Center Area in Wulanggitang District, East Flores Regency - Antonius Hendrikus Suban Liwu; Yuliana Radja Riwu; Helga J.N. Ndun (Lontar : Journal of Community Health, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis that can be transmitted by spraying it with sputum. The fight against TB in Indonesia started with the DOTS system in 1995. Puskesmas Boru has a fluctuating incidence of TB cases, up to 14 cases in 2018, 16 cases in 2019, and 15 cases in 2015. This study aimed to determine the implementation of the TB control program with DOTS strategy in the age of the COVID-19 pandemic at the Boru Health Center. This type of research is qualitative research with a phenomenological approach. This study has ten informants, namely the East Flores Regency P2P health service officers; Boru Health Center directors; Boru Health Center TB program owners; Boru Health Center laboratory directors; Drug Administration Supervisors; and patients in treatment. The results showed that implementing the DOTS strategy in the Boru Health Center had not gone optimally. This is evident from the unavailability of rapid molecular test kits at the Boru Health Center, and many suspects are afraid to do a sputum test due to the Covid-19 problems. It is hoped that the East Flores District Health Department and Boru Health Center will increase skilled health workers and provide socialization for TB suspects and patients related to the COVID-19 situation around anxiety and review readiness.